An Exploration into Nurses’ Experiences Regarding Ideal Clinic Realisation and Maintenance Programme Implementation in eThekwini District - (:unkn) unknown (My University, 2024)
Ideal Clinic Realisation and Maintenance Programme (ICRMP) is one of several quality improvement initiatives implemented in South Africa aimed at improving quality health care services provision, especially at the primary health care (PHC) level The South African National Department of Health introduced the ICRMP in response to challenges experienced in PHC services and to lay a strong foundation for the National Health Insurance implementation. The progress report 2015–2016 on the implementation of this programme indicated that achieving the 50% target in selected vital areas such as staffing, resource allocation, and utilisation was not achieved. This study was conducted in 18 PHC clinics in eThekwini district, KwaZulu-Natal aimed to explore and describe nurses’ experiences regarding the ICRM implementation. An exploratory descriptive, contextual qualitative design was employed guided by Donabedian’s structure, process, and outcomes model. Data were collected using semi-structured interviews with 24 nurses between 15 September and 25 October 2020 following receipt of ethics and analysed using Tesch’s open coding approach. It is evidenced in research that infrastructure is important in supporting the fundamental aim of promoting improved standards of care and well-being for all patients, and a good experience of the healthcare system by healthcare users. The three themes that emerged included structural limitations, processes involved in running the clinic, and support offered to the PHC clinics. These were highlighted as challenges experienced by nurses during the implementation of an ICRMP. Nurses’ negative experiences and perceptions made it difficult for them to accomplish the ICRMP standards. The findings from the study highlighted critical actions by the health care institution management which if instituted, could facilitate improved implementation of the ICRMP and achievement of the 50% target in selected vital areas. Nurses’ negat
Keywords: African Research